The Effect of Inflation and Exchange Rates on Interest Rates 2013-2022 - Aini, Lathifah; Saajidah, Annisa; Nasution, Putri Andini; Salsabila, Salsabila; Sari, Yolanda Novita; Silaban, Putri Sari Margaret Julianti (Perpustakaan dan Penerbitan Unismuh Makassar, 2024)
Inflation affects the real income of individuals who have a fixed income, which in turn impacts the wealth stored in banks. Various factors, such as interest rates, inflation, and government economic policies, can influence the exchange rate. These three variables are closely interrelated, and changes in one can significantly affect the others. This research aims to analyze the effect of inflation and exchange rates on interest rates. The results of this study are expected to provide valuable information and input for the central bank in determining effective interest rate policies to stabilize the economy. The research method employed is a quantitative approach utilizing time series data. This type of data is essential for analyzing trends and applying simple regression techniques to observe relationships between variables. Data used in this study were collected from Bank Indonesia for the period 2013-2022. The analysis reveals varying regression coefficients: a negative regression coefficient indicates a negative relationship between variable X and Y, meaning that an increase in one variable leads to a decrease in the other. Conversely, a positive regression coefficient signifies a positive relationship, where an increase in one variable results in an increase in the other. By understanding these relationships, policymakers and stakeholders can make informed decisions regarding monetary policy and economic strategies. This research contributes to a deeper understanding of how inflation, exchange rates, and interest rates interact, helping to ensure a stable financial environment that benefits individuals and institutions alike.